2020
DOI: 10.1007/s00415-020-10144-7
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year clinical follow-up study from the Italian National Registry for FSHD

Abstract: Background The natural history of facioscapulohumeral muscular dystrophy (FSHD) is undefined. Methods An observational cohort study was conducted in 246 FSHD1 patients. We split the analysis between index cases and carrier relatives and we classified all patients using the Comprehensive Clinical Evaluation Form (CCEF). The disease progression was measured as a variation of the FSHD score performed at baseline and at the end of 5-year follow-up (ΔFSHD score). Findings Disease worsened in 79.4% (112/141) of inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
(64 reference statements)
0
20
0
Order By: Relevance
“…Another valuable aspect of the MOMIS FSHD Web Platform is the ability to carry out family studies, de ning in each family the characteristics of the proband and relatives. As shown in Table 1, the platform has been successfully applied to many different aspects of FSHD research, starting from the CCEF validation [15] to genotype/phenotype characterization of people carrying speci c molecular features: 1-3 DRA [13] or 7-8 DRA [20] or 9-10 [21] and to follow up studies [22].…”
Section: The Momis Fshd Web Platform Application In Clinical Researchmentioning
confidence: 99%
“…Another valuable aspect of the MOMIS FSHD Web Platform is the ability to carry out family studies, de ning in each family the characteristics of the proband and relatives. As shown in Table 1, the platform has been successfully applied to many different aspects of FSHD research, starting from the CCEF validation [15] to genotype/phenotype characterization of people carrying speci c molecular features: 1-3 DRA [13] or 7-8 DRA [20] or 9-10 [21] and to follow up studies [22].…”
Section: The Momis Fshd Web Platform Application In Clinical Researchmentioning
confidence: 99%
“…However, the slopes of MNF and FD during the endurance contraction differed between the two categories of FSHD (A and Not A), suggesting that patients with facial and scapular girdle muscle weakness experienced greater fatigue during isometric elbow flexion compared to the other patients. The two categories share pathophysiologic traits including impaired abduction of the upper limb with winged scapula and varying degrees of facial weakness (Ricci et al, 2016), which reflect a worsening phenotype (Vercelli et al, 2021). Importantly, the greater declines in the slopes of MNF (which is related to decreased muscle fiber CV and increased MU firing rate and synchronization (Bigland-Ritchie and Woods, 1984;Brody et al, 1991;Gabriel and Kamen, 2009) and FD (which is related to increased MU firing rate and synchronization Rampichini et al, 2020) suggest that the difference in fatigability between A and Not A is mainly due to central factors.…”
Section: Influence Of Sex Fshd Category Asymmetry Of Muscle Involvement and Scapular Girdle Involvement Score On Fatigabilitymentioning
confidence: 99%
“…Moreover, several genotype-phenotype correlation studies reported a rough inverse correlation between the number of D4Z4 repeats and the severity of FSHD (Lunt et al, 1995;Tawil et al, 1996;Ricci et al, 1999). However, more recent publications did not find satisfactory correlations, even using a large number of patients (Ruggiero et al, 2020;Salort-Campana et al, 2020;Vercelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Projects dedicated to genetic diagnosis and geno-phenotype correlation led to the characterization of large disease-specific patient cohorts [12][13][14][15][16][17][18][19][20]. In addition to increasing disease knowledge, these studies contributed to identifying patients and families still missing a genetic diagnosis that underwent new genetic examination, with many families receiving appropriate genetic counselling [21][22][23][24].…”
Section: Outcomes Of the Studiesmentioning
confidence: 99%
“…The genetic and clinical characterisation of large patient cohorts has had a broad impact nationwide on providing genetic diagnosis, inform about prognosis, and facilitate genetic counselling and decision making [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The investment in genomic research allowed to identify new mutations and new genes not yet included in the genetic services provided by the national health system, exploring what Horton and Lucassen defined "a hybrid space where clinical practice and research need to co-exist" [64].…”
Section: Impact On Diagnosismentioning
confidence: 99%